Damage Characteristics Caused by Deep-Hole Blasting near Normal Fault and Its Effects on Coal and Gas Outbursts. (13th April 2022) - Gao, Kui; Qiao, Guodong; Liu, Zegong; Xia, Wei
Abstract : To understand the stability of coal and rock in areas of normal faults disturbed by the dynamic loads of blasting, the damage characteristics of coal and rock within a normal fault are investigated using similarity simulation tests. The mechanism for coal and gas outbursts within a normal fault is analyzed theoretically, and the results indicate that the maximum tensile stress in the vertical direction of the blasting hole in the normal-fault model is 1.17 times that in the no-fault model. The propagation of cracks near the blasting hole produces crushing circles, and more cracks are produced in the normal-fault model, causing severe damage to the coal seam and floor rock adjacent to the upper wall of the normal fault. Meanwhile, coal on the surface of the coal seam falls off. The cracks extend to the roof rock through the footwall of the normal fault. Cracks in the adjacent strata and coal seam interpenetrate those around the blasting hole, which is a potentially dangerous area for coal and gas outbursts. The cumulative damage caused by blasting vibrations increases the extent and scope of the damage to coal and rock, and broken coal and rock provide weak surfaces and gas flow channels that can lead to dynamic gas disasters. The research results will provide a theoretical basis for gas dynamic disasters induced by blasting disturbance in normal fault structures. Based on cases of coal and gas outbursts in the Didaoshenghe Coal Mine in Heilongjiang Province, China, an important reason for such incidents is considered to be the blasting areas of normal faults being disturbed by air-powered coal drilling.